Comparison of the FilmArray Respiratory Panel and Prodesse Real-Time PCR Assays for Detection of Respiratory Pathogens - Loeffelholz, M. J. (American Society for Microbiology, 2011)

(untitled)
We compared the diagnostic performance and overall respiratory pathogen detection rate of the premarket version of the FilmArray Respiratory Panel (RP) multiplex PCR assay (Idaho Technology, Inc., Salt Lake City, UT) with those of the Food and Drug Administration (FDA)-cleared Prodesse ProFlu+, ProFAST+, ProParaflu+, Pro hMPV+, and ProAdeno+ real-time PCR assays (Gen-Probe, San Diego, CA). The assays were performed on a panel of 192 nasopharyngeal-secretion specimens collected from 81 children under 1 year of age with upper respiratory tract symptoms. To resolve discordant results and confirm pathogens detected only by the larger FilmArray panel, we performed laboratory-developed real-time PCR assays. Among viruses detectable by both commercial assays (adenovirus, human metapneumovirus, influenza A virus, influenza B virus, parainfluenza viruses 1 to 3, and respiratory syncytial virus), the FilmArray and Prodesse assays showed good overall agreement (181/192 [94.3%]; kappa = 0.87; 95% CI, 0.79 to 0.94). FilmArray RP detected more parainfluenza viruses 1 and 3 than ProParaflu+ (18 versus 13) while ProAdeno+ detected more adenoviruses (11 versus 6), but these differences were not statistically significant. Additionally, FilmArray RP detected 138 pathogens (confirmed as true positives) not included in the Prodesse assays (rhinovirus [RV]/enterovirus [EV], 118; bocavirus, 8; coronavirus, 7; parainfluenza virus 4, 4; Mycoplasma pneumoniae, 1). FilmArray RP was cleared by the FDA following the completion of this study. The FDA-cleared version includes the following targets: adenovirus, coronaviruses HKU1 and NL63, human metapneumovirus (hMPV), influenza A virus (to type level only), influenza A H1 seasonal virus, influenza A H3 seasonal virus, influenza A virus H1-2009, influenza B virus, parainfluenza viruses 1 to 4, respiratory syncytial virus (RSV), and RV/EV (no differentiation). The larger panel in the FilmArray RP assay allowed the detection of additional respiratory pathogens compared to the Prodesse assays. In this population of young children with upper respiratory tract infection, RV/EV accounted for the majority of the additional pathogens detected by FilmArray RP.